The Rambling Guitarist - Saito, Buichi; Takamura, Kuratarô; Kobayashi, Akira; Asaoka, Ruriko; Nakahara, Sanae (Arrow Video, 2016)
In Saito's "The Rambling Guitarist", mega star Akira Koabyashi (Battles Without Honour and Humanity) stars as wandering street musician Shinji, who falls in with mob boss Akitsu after saving one of his henchmen in a bar fight. Tasked by Akitsu with evicting an offshore fishery, Shinji finds himself in the middle of a very unusual domestic dispute ... [Cover]
Keywords: DVD-Video